Review on plant-derived bioactive peptides: biological activities, mechanism of action and utilizations in food development - Fan, Hongxiu; Liu, Hongcheng; Zhang, Yanrong; Zhang, Shanshan; Liu, Tingting; Wang, Dawei (Journal of future foods, 2022)
Plant proteins are good alternative to animal sources in bioactive peptide production due to their safety, low-cost, rich resources and easy for large scale production. The bioactivities of the peptides derived from plant proteins including antihypertensive, hypocholesterolemic, immunomodulatory, antioxidant, antimicrobial, anti-diabetic, opiate and hepatoprotective effect are being increasingly recognized with regards to health promoting and disease prevention. In addition to bioactivities, the plant-derived bioactive peptides possess various functional properties including emulsifying and foaming properties, and water and oil retention capacities owning to the hydrophilic/lipophilic property, conformational flexibility and chain length of peptides. Hence, the plant-derived bioactive peptides are promising ingredients for the development of health-care and functional products. This review provides the research progress on the biological activities and functional properties of plant derived peptides. The mechanism of action and structure-activity relationships of the bioactive peptide were also described, when known. Furthermore, recent developments, major challenges and prospect in the application of the plant-derive bioactive peptides in the development of functional products are discussed and summarized. The objective of this review is to improve the understanding of plant-derive bioactive peptides, and provide some constructive inspirations for further research and industrial application in the food and medicine industry.